TPACK-Based Learning Management Training for Batch 2 Pekerti University of Bengkulu - Risdianto, Eko; Fitria, Jeni (CV Media Inti Teknologi, 2023)
This activity aims to train lecturers in managing TPACK-based learning through the PEKERTI (Basic Instruction Technique Skills Improvement) Batch 2 2023 program.The activity was carried out in March 2023 at Bengkulu University, with a total of 39 participants in the training who were lecturers from different tertiary institutions. The research instrument used was a closed questionnaire with 4 answer choices. The data analysis technique used is descriptive statistical analysis. PEKERTI participant response analysisrelated to training activitiescarried out on the data obtained in the form of a percentage. Percentages are obtained based on modified Likert Scale calculations. The results showed that more than 50% of the respondents were in the Strongly Agree category based on the guidelines in table 4 of the Likert scale interpretation. As for the disagree and strongly agree categories, the number is 0 respondents. This means that the respondents who were the sample in this study only gave answers that strongly agreed and agreed to the 19 positive statements submitted in the questionnaire developed with reference to PEKERTI batch 2 activities in 2023 at the University of Bengkulu. So, it can be concluded that the TPACK-based learning management training in Pekerti Batch 2 at the University of Bengkulu received a positive response from the participants.